'Straight-looking, straight-acting': countering effemiphobia in acting training. Issue 1 (2nd January 2017) - Alexandrowicz, Conrad
Abstract : What is to become of the 'effeminate' actor? This essay focuses on the subject of gender-based discrimination with reference to male acting students, and proposes that, despite the huge social and legal gains made on behalf of various sexual minorities, the professional theatre in Canada and the US ‒ including the training institutions that support and feed it ‒ is engaged in the practice of reinforcing normative performances of gender. As David Eulus Wiles argues in his essay in The Politics of American Actor Training, we have imported the discriminatory patterns of the 'entertainment industry' into the theatre programmes of academic institutions that explicitly forbid such discrimination. The article proposes that part of addressing this problem in a meaningful way would entail transformations in the approach to the training of actors, in particular replacing classic text-based approaches with psychophysical methods, such as Laban Movement Analysis. Exploring the research into gender construction by performance artist and drag king Diane Torr, the paper speculates about how such transformations in training would necessitate concomitant changes in the practice of the art form itself, ushering in a new plurality of approaches and expressions, in particular in the realm of department productions. This argument is supported with reference to a consideration of how a renewed connection with the theory of Bertolt Brecht could serve the aims of gender critique, referring to positions taken by Jill Dolan, Sue-Ellen Case, Richard Schechner and Elin Diamond.